PREDIKSI KEBUTUHAN AIR BERSIH PDAM TIRTA MUSI PALEMBANG (STUDI KASUS WTP BORANG) - Martini, RA Sri; Agusri, Erny; Setiawati, Mira (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
PDAM Tirta Musi Palembang is a government-owned enterprise engaged in water treatment services,where water that is not dirty is processed and converted into clean water that is ready and suitable forhuman consumption. The increase in annual population has an impact on the increasing growth in thenumber of customers who need clean water. However, the Water Treatment Plant (WTP) or WaterTreatment Plant (IPA) still does not provide full services to all city environments, one of which is at thePalembang City Form WTP. The source of WTP processing comes from the Borang River and intake 1 ilir.The customer population is projected to increase to 22,434 in 2023 based on Geometric analysis with acalculation of customer needs of 218.04 liters/second. The pump used at WTP Borang has a capacity of200 liters / second and uses 2 pumps, so WTP Borang can still meet customer needs. The amount of waterdischarge required during maximum days and peak hours is 239.84 liters / second and 327.06 liters /second respectively. With this situation, it is predicted that the community's clean water needs in 2023 canbe fulfilled by WTP Borang.